A new cynodont from the Upper Triassic Los Colorados Formation (Argentina, South America) reveals a novel paleobiogeographic context for mammalian ancestors - Gaetano, Leandro Carlos (2022)
Probainognathia is a derived lineage of cynodonts which encompass Mammalia as their crown-group. The rich record of probainognathians from the Carnian of Argentina contrasts with their Norian representation, with only one named species. Here we describe a new probainognathian, Tessellatia bonapartei gen. et sp. nov., from the Norian Los Colorados Formation of the Ischigualasto-Villa Unión Basin of Argentina. The new taxon, represented by a partial cranium with associated lower jaws, was analyzed through neutron and X-rays micro-tomography (μCT). The high-resolution neutron μCT data allowed the identification of a unique character combination, including features inaccessible through traditional techniques. We constructed the largest phylogenetic data matrix of non-mammalian cynodonts. The new species and its sister taxon, the Brazilian Therioherpeton cargnini, are recovered as probainognathians, closely related to Mammaliamorpha. We conducted the first quantitative paleobiogeographic analysis of non-mammalian cynodonts, focusing in probainognathians. The results indicate that Probainognathia and Mammaliamorpha originated in southwestern Gondwana (in the Brazilian Paraná Basin), which was an important center of diversification during the Triassic. Finally, the Chinese Lufeng Basin is identified as the ancestral area of Mammaliaformes. These new findings, besides adding to the knowledge of the poorly represented Norian cynodonts from the Los Colorados Formation, are significant to improve our understanding of probainognathian diversity, evolution, and paleobiogeographic history.